Respuesta :
Answer:
22
Step-by-step explanation:
You are given term is equal to previous term plus 6.
a1=10
a2=10+6=16
a3=16+6=22
Answer:
The correct answer is 22
Step-by-step explanation:
We have that [tex]a_{1}[/tex] is 10
and the general formule is an= [tex]a_{n-1}[/tex] +6
taking n=3 and replacing it on the general equation, we have:
[tex]a_{3}[/tex] = [tex]a_{2}[/tex] +6 (1)
We don't know the term [tex]a_{2}[/tex], we can look for it occupying the general equation again:
[tex]a_{2}[/tex] = [tex]a_{1}[/tex] +6 (2)
Replacing [tex]a_{1}[/tex] on (2):
[tex]a_{2}[/tex] = 10 +6 = 16 (3)
And finally replacing (3) on (1) we get te correct answer;
[tex]a_{3}[/tex] = 16+6 = 22